2022
DOI: 10.1021/jacsau.2c00322
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Dual-Function Hybridized MetalOrganic Capsules to Enzymes for Cascade Catalysis

Abstract: The combination of chemo- and biocatalysis for multistep syntheses provides attractive advantages in terms of evolvability, promiscuity, and sustainability striving for desirable catalytic performance. Through the encapsulation of flavin analogues by both NADH and heme mimics codecorated heteroleptic metal – organic capsules, herein, we report a progressive host – guest strategy to imitate cytochrome P450s catalysis for cascade oxidative coupling catalysis. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Owing to the involvement of multiple metal sites that facilitate multi-electron transfer and spin transition, binuclear or trinuclear Cu centers are a major class of cofactors that bind and activate O 2 in many oxidases including cytochrome c oxidase, tyrosinase, catechol oxidase, laccase, etc. It has been long of interest mimicking the function of these oxidases in an artificial system and promoting aerobic oxygen utilization in organic reactions, yet many of these artificial enzymes only exhibited limited activity and reaction/substrate scope so far.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the involvement of multiple metal sites that facilitate multi-electron transfer and spin transition, binuclear or trinuclear Cu centers are a major class of cofactors that bind and activate O 2 in many oxidases including cytochrome c oxidase, tyrosinase, catechol oxidase, laccase, etc. It has been long of interest mimicking the function of these oxidases in an artificial system and promoting aerobic oxygen utilization in organic reactions, yet many of these artificial enzymes only exhibited limited activity and reaction/substrate scope so far.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] In the DEL library, each compound is connected to a unique, amplifiable DNA tag, simplifying chemical identification following selection against biomolecular targets. [ 5 ] So far, a series of hits have been efficiently selected from DELs, [ 6 ] targeting different types of drug targets such as enzymes, [ 7–13 ] kinase, [ 14 ] chemokines, [ 15 ] G protein‐coupled receptors (GPCRs), [ 16,17 ] protein and protein interactions (PPIs), [ 18–20 ] and RNA. [ 21–24 ] Furthermore, DEL has emerged became a fundamental platform to bridge chemistry and biology beyond the hit selection activity in innovative drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…36 Cai et al reported a cytochrome P450-mimetic metal organic framework that works in tandem with dehydrogenases, which is a photo-, chemo-, and biocatalytic hybrid, for C(sp 2 )−H functionalization. 37 In this study, we report a "three-stage (bioelectrocatalysis− biocatalysis−organocatalysis)" system that couples a bioelectrocatalytic multienzyme cascade with single amino acid-based organocatalysis for the sequential functionalization of nheptane to 1-heptanol, heptanal, and eventually the corre- sponding α-hydrazino aldehyde (Figure 1). The cathodic chamber contains an alkane monooxygenase (alkB, E C 1.14.15.3) from Pseudomonas putida GPO1, 38 a rubredoxin (alkG) protein from P. putida GPO1, 38 an engineered choline oxidase (AcCO 6 , E C 1.1.3.17) from Arthrobacter cholorphenolicus, 39 and a catalase (CatA, EC 1.11.1.6) from Bacillus subtilis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tandemly-used enzymes and photocatalysts (e.g., porphyrins and sodium AQ-2-sulfonate) have been reported for C–H hydroxylation, halogenation, amination, and ketone formation . Cai et al reported a cytochrome P450-mimetic metal organic framework that works in tandem with dehydrogenases, which is a photo-, chemo-, and biocatalytic hybrid, for C­(sp 2 )–H functionalization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation